The cultural psyche : the selected papers of Robert A. LeVine on psychosocial science - LeVine, Robert A. 1932- (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"As envisaged by Robert A. LeVine many years ago, the human development indicators have improved in many societies as income, healthcare and educational opportunities have been enlarged. Global transformations have led to significant decline in extreme poverty and an increase in working class and middle class families around the world in the emerging economies throughout Africa and Asia. As the technological and global influences continue to challenge the dominant narrative in academic psychology, conflated with WEIRD data assumptions, interdisciplinary research will continue to increase in value and scope, where LeVine's classical approach in psychological anthropology, combined with psychoanalysis, developmental psychology, demography, language or area research and population studies, offers a path forward. The essays collected here in addition to honoring LeVine's work, hold out the promise of a real convergence between psychology and anthropology or the development of a psychosocial science -- a confluence between positivism and relativism, empiricism and ethnography, and social sciences and human sciences. The scientific search for universal laws and the ever expanding search for cultural meanings in the diverse communities around the world must continue simultaneously and in conjunction with the transnational or global challenges we face today. As psychologists embrace the larger human laboratory in the real-world field settings, the advances made by psychological anthropology over the past half-century will continue to provide an important guide for forays into the uncharted territories. Locating the psyche in culture has the real possibilities of advancing the discipline of psychology from within and without. On the one hand, greater emphasis on 'subjectivity in anthropology' will lead to newer lines of studies that advance what Robert LeVine called "person centered ethnography," while the greater emphasis on the brain, neuroscience and genomics might fuel studies on epigenetics, plasticity and human growth and maturation in cultural context, or what LeVine has termed the "biocultural" or "biopsychosocial" model of human development. Hybridity fostered by interdisciplinary researchers has stood the test of time as the social sciences have gradually outgrown the monolithic ways of looking at the world. The project of a psychosocial science represented by the work of Robert A. LeVine at the intersection of psychology, anthropology, demography, child development and psychoanalysis maps out some of the challenges of a hybrid discipline. Hybridity impacts not only the humanities and social sciences, but physical sciences in genetics and genomics, or applied disciplines like biotechnology and life sciences. Thus, it is important that we not lose sight of LeVine's spirit of interdisciplinary research. Advocates for universalism, the psychologists or behavioral scientists pursuing universal laws of human nature, must collaborate with the growing number of relativistic scientists - anthropologists, sociologists, or cultural studies experts -- searching for local meanings in small-scale village communities. There will be a confluence of social and human sciences, or what C.P. Snow, the English literary critic called the 'two cultures' of the scientific revolution - the sciences and humanities"--